2015
DOI: 10.1007/s00204-015-1566-x
|View full text |Cite
|
Sign up to set email alerts
|

Human metabolism and excretion kinetics of aniline after a single oral dose

Abstract: Aniline is an important source material in the chemical industry (e.g., rubber, pesticides, and pharmaceuticals). The general population is known to be ubiquitously exposed to aniline. Thus, assessment of aniline exposure is of both occupational and environmental relevance. Knowledge on human metabolism of aniline is scarce. We orally dosed four healthy male volunteers (two fast and two slow acetylators) with 5 mg isotope-labeled aniline, consecutively collected all urine samples over a period of 2 days, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Aniline is used in shellacs for wood coloring; thus, construction painters and finishing workers are potentially exposed. Aniline is metabolized in paracetamol, which is an antiandrogen substance [ 36 , 37 ], causing hormonal disturbances [ 99 ].…”
Section: Discussion On Eds In Construction and Plastic Industry Tementioning
confidence: 99%
See 1 more Smart Citation
“…Aniline is used in shellacs for wood coloring; thus, construction painters and finishing workers are potentially exposed. Aniline is metabolized in paracetamol, which is an antiandrogen substance [ 36 , 37 ], causing hormonal disturbances [ 99 ].…”
Section: Discussion On Eds In Construction and Plastic Industry Tementioning
confidence: 99%
“…In this short communication, the construction and plastics industries were selected as examples of two sectors, in which many workers across Europe are exposed to EDs. These include phthalates, bisphenols, aniline, cadmium and chromium [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: The Need For a New Paradigm In Occupational Healthmentioning
confidence: 99%
“…Targeted analyses of APAP in blood plasma and urine APAP was analyzed using an adapted version of a method previously described (Modick et al, 2013;Modick et al, 2016). Unlabeled APAP (NA4AP) was used for calibration (the mass transition m/z 152  110 was used for quantification and m/z 152  93 was used as qualifier) and APAP-d4 (NA4AP-d4) was used as internal standard (same mass transitions as reported in Modick et al (Modick et al, 2016)). The gradient for the analytical separation was modified, starting at 15% solvent B (acetonitrile containing 0.05% formic acid).…”
Section: Collection Of Blood Plasma and Urine Samples Before And Aftementioning
confidence: 99%
“…Whilst most of circulating paracetamol in humans comes from use of paracetamol-containing medications, an alternative source has also been described. The industrial chemical aniline, which is found in a wide variety of manufactured products, such as rubber, pharmaceuticals, cosmetics and cigarette smoke, is rapidly metabolized to paracetamol inside the body (Modick et al , 2014, 2016). Furthermore, in-vivo studies in which male mice exposed in utero to aniline have shown similar fetal anti-androgenic effects to those described for exposure to paracetamol (Holm et al , 2015).…”
Section: Pharmaceuticalsmentioning
confidence: 99%